PERBEDAAN PENGARUH METODE MENGAJAR RECIPROCAL DAN SELF CHECK TERHADAP PENINGKATAN KETERAMPILAN TEKNIK DASAR BOLAVOLI - Tri Saptono (Departement of Sports Education, Faculty of Sport Sciences Yogyakarta State University, 2013)
This research aims to find out the difference effect of reciprocal method and self check method on the basic skilltechnic of volleyball. The population of the research consists of 60 male students at UPN “Veteran” Yogyakarta, with40 students as random samples which then divide into two groups. First group is reciprocal method and second groupis self check method. Based on data analysis technique it gets t observation: 13.198 Mean while for t. table = 4.11 (tobservation: 13.198 t count 4.11). Based on the result of the analysis, conclusions are drawn as follows that thereis a significant difference between reciprocal method and self check method on the basic skill technic of volleyball.Keywords: Reciprocal, Self Check, Volleyball